Multiple cutaneous swellings in an immunocompetent host: cryptococcosis overlooked - Kosaraju,Kranthi (2011)
Recently, there has been an increase in the incidence of cryptococcosis even among immunocompetent patients. We present a case of multiple subcutaneous swellings later developing into a non-healing ulcer caused by Cryptococcus in a 60 year-old immunocompetent male along with a brief review of clinical presentations of cutaneous cryptococcosis in immunocompetent and immunocompromised individuals. A high index of suspicion is desired in view of possible dissemination and variable non-specific clinical presentations.